Integrative developmental biology in the age of anthropogenic change. Issue 4 (13th April 2021) - Sanger, Thomas J.
Abstract: Humans are changing and challenging nature in many ways. Conservation Biology seeks to limit human impacts on nature and preserve biological diversity. Traditionally, Developmental Biology and Conservation Biology have had nonoverlapping objectives, operating in distinct spheres of biological science. However, this chasm can and should be filled to help combat the emerging challenges of the 21st century. The means by which to accomplish this goal were already established within the conceptual framework of evo‐ and eco‐devo and can be further expanded to address the ways that anthropogenic disturbance affect embryonic development. Herein, I describe ways that these approaches can be used to advance the study of reptilian embryos. More specifically, I explore the ways that a developmental perspective can advance ongoing studies of embryonic physiology in the context of global warming and chemical pollution, both of which are known stressors of reptilian embryos. I emphasize ways that these developmental perspectives can inform conservation biologists trying to develop management practices that will address the complexity of challenges facing reptilian embryos. Abstract : The integration of developmental studies with Conservation Biology can be field‐first studies that begin with observations in natural ecosystems or lab‐first studies that proactively explore the effects of potential embryonic stressors. Although independent, these approaches can and should inform one another. The lab‐first approach is necessary for predicting the effects of future stressors, while the field‐first is critical for understanding the challenges facing wildlife today. A strong comparative framework complete with information about the embryological thresholds and limits of the compensatory mechanisms of multiple species will strengthen the predictive certainty of models foreshadowing future impacts of anthropogenic change on wildlife. Research Highlights: Reptiles and their embryos are under threat of emerging anthropogenic change such as pollution and thermal stress. Herein, I outline areas of future research where greater information about reptilian development in the context of real‐world challenges may inform conservation efforts.